Effectiveness of Performance of Government Internal Supervisory Apparatus (APIP) in Utilizing E-Audit - Munfarida Rizky Mutamimmah; Taufik Kurrohman; Alfi Arif (International Journal of Economics, Management and Accounting, 2025)
This study aims to determine the effectiveness of the performance of the Internal Supervisory Apparatus of the Banyuwangi Regency Government in utilizing e-audit and to determine user expectations in utilizing e-audit in the internal supervision process in Banyuwangi Regency. This study is an exploratory study using a mixed qualitative and quantitative approach. The data collection method used in this study is the triangulation method, namely data collection through interviews while testing the validity of the data to parties related to the use of e-audit. Interviews were conducted on December 2, 3, 4 and 6, 2024, which showed that the effectiveness of APIP performance in utilizing e-audit was quite effective or obtained a value of 55 out of a maximum value of 100. So that four of the five components that are indicators of effectiveness assessment still need a lot of development to be able to meet the needs and expectations of users in achieving supervisory objectives, including the preparation of PKPT, implementation, reporting and monitoring of follow-up supervision results.